Study guides

☆☆

Q: What is -3b plus 3c plus 5-b-8c-4?

Write your answer...

Submit

Still have questions?

Related questions

2ab - 6ac + 3b - 9c = 2a(b - 3c) + 3(b - 3c) = (2a + 3)(b - 3c).

4a + 3c - 2b - c + a - b = 5a - 3b + 2c

2ab - 6ac + 3b - 9c = b(2a + 3) - 3c(2a + 3) = (b - 3c)(2a + 3)

0.6b + 3c

Gathering like terms together, this is equal to 5a + 3b + 7c.

(2a + 3)(b - 3c)

3b

(3b + 7x)(3b + 7x) or (3b + 7x)2

(a+b)(3b+1)

5 + 10ac + 3b

6+7a+6b

(2a + b)(a + 3b)

3c-d

4c+2 = 3c+9 4c-3c = 9-2 c = 7

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

1a+3b 2a+4b=3a +7b

8a+b+32a+3b=40a+4b

6c.

2A plus 3B times 2A - 3B = 4A2 - 9B2; this is an example of the general formula (a + b)(a - b) = a2 - b2.

-6(a-3b-9c)

3c+6=18 3c+6-6=18-6 3c=12 3c÷3=12÷3 c=4

11a+7b-(3b-2a)

3b + 6 = 12 3b = 6 b = 2

12